Estimated prevalence and incidence of hypersensitivity pneumonitis in Japan - Tsukasa Okamoto; Mariko Hanafusa; Taketomo Abe; Takashi Shimamura; Masaru Ito; Yoko Wakai; Torahiko Jinta; Katsuyuki Higa; Yasuhiro Kondoh; Yasumi Okouchi; Ryo Okuda; Masashi Bando; et al. (Allergology International)
Background: The latest guidelines on hypersensitivity pneumonitis (HP) categorise the disease as either fibrotic or non-fibrotic because of the greater clinical utility of this stratification. However, the prevalence and incidence of fibrotic and non-fibrotic HP are unknown. This study assessed the exact prevalence and incidence of fibrotic and non-fibrotic HP in Japan in 2021. Methods: For adults, the study hospitals were selected by stratified random sampling according to numbers of beds. The sampling rate was set at about 20%. The questionnaire survey was submitted to the target hospitals. For pediatric cases, a survey was distributed to all members of the Japanese Society of Pediatric Pulmonology and Japanese Society of Pediatric Allergy and Clinical Immunology. Results: Regarding adult cases, in total, 575 facilities responded to the survey, resulting in a response rate of 36.4%. The estimated prevalence and incidence of fibrotic HP were 6.3 and 2.5 per 100,000 population, respectively, versus 3.6 and 2.0 per 100,000 population, respectively, for non-fibrotic HP. Both fibrotic and non-fibrotic HP were more prevalent in southern Japan (Kyushu) and less prevalent in northern Japan (Hokkaido). The incidence of non-fibrotic HP was significantly lower in December than in the other months (relative risk ratio = 0.36, p < 0.001). Three cases of fibrotic HP and five cases of non-fibrotic HP were identified in children. Conclusions: This study determined the prevalence and incidence of fibrotic and non-fibrotic HP in Japan for the first time.